Synthesis of regularities of control of blocking properties of differential transmission mechanisms - A. V. Popov; S. V. Ushnurtsev; A. V. Keller (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The analysis of the operating conditions of four-wheel drive vehicles allows us to conclude that they are characterized by a continuously and significantly changing spread of the values of loads falling on the driving wheels, as well as the spread of resistance to movement and wheel adhesion to the bearing surface. In this regard, the degree of blocking of the inter-axle, inter-vehicle and inter-wheel connections should automatically change depending on the driving conditions, providing the car with the maximum reserve of traction forces with the minimum possible rolling resistance.